2015
DOI: 10.1016/j.gore.2015.06.005
|View full text |Cite
|
Sign up to set email alerts
|

FGFR3–TACC3: A novel gene fusion in cervical cancer

Abstract: Cervical cancer epitomizes the success of cancer prevention through the human papillomavirus (HPV) vaccine, but significant challenges remain in the treatment of advanced disease. We report the first three cases of cervical carcinoma harboring an FGFR3–TACC3 fusion, which serves as a novel therapeutic target. The fusion, identified by comprehensive genomic profiling, activates the FGFR pathway that has been implicated in HPV-driven carcinogenesis. One of the patients whose tumor contained the FGFR3–TACC3 fusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 16 publications
2
44
0
Order By: Relevance
“…Since their initial discovery in the late 1990s, the detection of these fusion proteins has steadily increased at a surprising rate. The focus of this article is a fusion protein consisting of FGFR3 fused to transforming acidic coiled-coil containing protein 3 (TACC3) that has been identified in glioblastoma, lung cancer, bladder cancer, oral cancer, head and neck squamous cell carcinoma, gallbladder cancer, and cervical cancer (1,2). The FGFR3-TACC3 fusion protein is a consequence of a 70 kb tandem duplication at 4p16.…”
Section: Introductionmentioning
confidence: 99%
“…Since their initial discovery in the late 1990s, the detection of these fusion proteins has steadily increased at a surprising rate. The focus of this article is a fusion protein consisting of FGFR3 fused to transforming acidic coiled-coil containing protein 3 (TACC3) that has been identified in glioblastoma, lung cancer, bladder cancer, oral cancer, head and neck squamous cell carcinoma, gallbladder cancer, and cervical cancer (1,2). The FGFR3-TACC3 fusion protein is a consequence of a 70 kb tandem duplication at 4p16.…”
Section: Introductionmentioning
confidence: 99%
“…FGFR1 amplification and FGFR fusion seem to be of key importance in tumor progression and were illustrated to be new drivers for a range of cancers [16,17]. It was reported that FGFR1 amplification was found in about 10% of breast cancer and located on chromosome 8p12 [18].…”
Section: Discussionmentioning
confidence: 99%
“…Patient selection by molecular foundation is not yet indicated for metastatic UC. Significant clinical responses were reported in FGFR3-TACC3 fusion-positive cervical cancer patients and glioma patients treated with an FGFR inhibitor[11][14]. However, the FGFR3 mutation is not very frequent among metastatic UC patients, comprising about 6–18% (2/35[38], 2/11[47], and 3/33[48]).…”
Section: Discussionmentioning
confidence: 99%
“…These include the S249C mutation in human BC cells 97–7[12], Y375C mutation in human BC cells MGH-U3[13], and FGFR3-TACC3 fusion in human glioma stem cells GIC-1123[11]. In addition, significant clinical responses to an FGFR inhibitor were reported in FGFR3-TACC3 fusion-positive patients with cervical cancer[14] or glioma[11] in Phase I clinical trials. Thus, detection of not only the activating FGFR3 mutations, especially in exons 7, 10 and 15, but also the FGFR3-TACC3 fusion in BC patients could be clinically important to identify responders to FGFR kinase inhibitors.…”
Section: Introductionmentioning
confidence: 99%